Spatio-temporal Characteristics of Drought in Different Growth Stages of Soybean in Heilongjiang - Gong Lijuan; Li Xiufen; Tian Baoxing; Wang Ping; Jiang Lanqi; Zhao Huiying (应用气象学报, 2020)
Heilongjiang is one of the main growing areas of soybean in China. Due to factors such as natural geographical location and climate, drought is one of primary determinant agro-meteorological disasters which constrains growth, development and the formation of soybean yield in Heilongjiang. Utilizing soil moisture data of 32 stations and soybean growth data of 26 stations from 1981 to 2017, the frequency of different grades of droughts, average intensity of drought, and drought risk indices are calculated. Spatio-temporal characteristics are analyzed from 5 regions in Heilongjiang, based on recognized hazard indicators on disaster grades of droughts for soybean from the meteorological industry standard which is released by China Meteorological Administration in 2018. Assessment and distribution of drought risk on the basis of occurrence frequency and intensity for soybean are pertained. Results show that the occurrence frequency of light drought is higher than that of severe and excessive drought for soybean. West region is an area where drought of soybean occurs frequently, centeral region takes the second place, and the other regions have relatively fewer drought occurrences. As for drought intensity, it's the highest in centeral region, the next is in west region, and the lowest drought intensity is in norht region. Moreover, the drought intensity in three-leaf to pod-bearing stage of soybean is higher than that in early and late growth stages in east, north and west regions. While in west and south regions, drought intensity during pod-bearing to maturity stage exceeds that in early stages. Drought risk indexes are negative. The lower number of risk index correlates with greater drought risk. The highest risk area is west region, the next is centeral region, and the last is norht region. It is an opportunity to seek the use of drought risk index as an indicator of drought risk of soybean. Considering the drought risk in different growth stages of soybean, the highest drought risk periods are flowering to pod bearing stages, and the drought risk of soybean is lowest in sowing to emerging stage. Areas of medium to high drought risk lie in the west of Songnen Plain and southwest of Sanjiang Plain in space through the whole growth period of soybean. And the others are low or slight drought risk regions. These results may provide guidance for soybean drought prevention, loss reduction and planting structure adjustment in Heilongjiang. It is strongly advised to strengthen the prediction and prevention of drought, especially in critical growth stages of soybean in two main plains.